Treatment of Food Aversion and Eating Problems in Children with Short Bowel Syndrome: A Systematic Review - Francesca Gigola; Virginia Carletti; Riccardo Coletta; Martina Certini; Marco Del Riccio; Caterina Bortolotti; Antonino Morabito (MDPI AG, 2022)
Food Aversion (FA) is a strong refusing behaviour to the oral assumption of food that can affect children with Short Bowel Syndrome (SBS). Management includes behavioural and Messy Play treatments, with few reports on systematic strategies to return the patient to enjoyable eating. We conducted a systematic review to better understand this complex and vital issue. (1) Materials and Methods: We investigated publications using MEDLINE, Embase, and the Web of Science to include articles published up to July 2022. The inclusion criteria were original articles including paediatric patients (aged < 18 years old) affected by SBS and Intestinal Failure (IF) who underwent treatment for FA. (2) Results: A total of 24 patients received treatment-15 (62.5%) patients were male and 9 (37.5%) were female. The age range was from 1 month to 16 years. Treatment of FA was carried out by behavioural therapy in 2 patients and Messy Play Therapy in 12 patients already surgically and pharmacologically managed for SBS. The treatment results showed complete weaning from Parenteral Nutrition in 9/14 cases (64%) using the behavioural treatment and 7/12 cases using Messy Play Therapy. (3) Conclusions: FA is a rare but disabling condition that often affects SBS patients, worsening their overall health and quality of life. This condition should be addressed in an Intestinal Rehabilitation Centre context. Our review sheds light on the literature gap regarding FA, and further studies are required to understand better which treatment options best suit SBS paediatric patients.